Find Length

Geometry Level 4

In quadrilateral A B C D , ABCD, A B = 6 , AB=6, A B C = 9 0 , \angle{ABC}=90^\circ, B C D = 4 5 \angle{BCD}=45^\circ and C A D = 2 A C B . \angle{CAD}=2\angle{ACB}. If D E DE is perpendicular to A C AC with E E on side B C , BC, find the length of C E . CE.


Bonus: Solve it without trigonometry.


The answer is 12.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Weiming Zheng
Aug 29, 2019

Draw line AG // BC; CG ⊥ BC; extend AD so it intersects CD at F. Since ∠DAC = 2β, so FC = 2CG = 2AE = 12.
Since θ = 180° - 45° - a = β + 45°; θ’ = 2β + 45° - β = β + 45°, so θ = θ', ΔED’C = ΔFD’C, & EC = FC = 12

Let A C B = θ \angle ACB = \theta . Drop a altitude from D D to B C BC and draw two straight lines parallel to B C BC through A A and D D . We note that D A G = E D F = θ \angle DAG = \angle EDF = \theta . Since C D F \triangle CDF is isosceles, D F = C F DF = CF ; let their length be h \color{#3D99F6} h . Then we have:

{ D F = D G + G F h = a tan θ + 6 . . . ( 1 ) C F = B C B F h = 6 tan θ a . . . ( 2 ) where A G = B F = a \begin{cases} DF = DG + GF & \implies h = a \tan \theta + 6 & ...(1) \\ CF = BC - BF & \implies h = \dfrac 6{\tan \theta} - a & ...(2) \end{cases} \quad \small \color{#3D99F6} \text{where }AG = BF = a

From ( 1 ) + tan θ × ( 2 ) : h + h tan θ = 12 h = 12 1 + tan θ (1) + \tan \theta \times (2): \quad h + h \tan \theta = 12 \implies h = \dfrac {12}{1+\tan \theta}

Now C E = C F + E F = h + h tan θ = 12 1 + tan θ × ( 1 + tan θ ) = 12 CE = CF + EF = h + h \tan \theta = \dfrac {12}{1+\tan \theta} \times (1+\tan \theta) = \boxed {12} .

David Vreken
Aug 5, 2019

Place the diagram on a coordinate system so that B B is at the origin, C C is on the x x -axis, and A A is on the y y -axis. Let θ = A C B \theta = \angle ACB .

By trigonometry on A B C \triangle ABC , B C = 6 tan θ BC = \frac{6}{\tan \theta} .

Line C D CD has a slope of 1 -1 and an x x -intercept (and a y y -intercept) of 6 tan θ \frac{6}{\tan \theta} , so its equation is y = x + 6 tan θ y = -x + \frac{6}{\tan \theta} .

Line A D AD has a slope of tan ( ( 90 ° θ ) + 2 θ 90 ° ) = tan ( θ ) \tan((90° - \theta) + 2\theta - 90°) = \tan(\theta) and a y y -intercept of 6 6 , so its equation is y = ( tan θ ) x + 6 y = (\tan \theta)x + 6 .

Lines A D AD and C D CD intersect at D ( t , u ) D(t, u) , where t = 6 ( 1 tan θ ) tan θ ( 1 + tan θ ) t = \frac{6(1 - \tan \theta)}{\tan \theta (1 + \tan \theta)} and u = 12 1 + tan θ u = \frac{12}{1 + \tan \theta} .

Line A C AC has a slope of tan ( 180 ° θ ) = tan θ \tan(180° - \theta) = -\tan \theta .

Since D E A C DE \perp AC , D E DE has a slope of 1 tan θ \frac{1}{\tan \theta} , and since it goes through ( t , u ) (t, u) , its equation is y = 1 tan θ ( x t ) + u y = \frac{1}{\tan \theta}(x - t) + u .

Solving 0 = 1 tan θ ( x t ) + u 0 = \frac{1}{\tan \theta}(x - t) + u gives x = 6 tan θ 12 = B E x = \frac{6}{\tan \theta} - 12 = BE .

Therefore, C E = B C B E = 6 tan θ ( 6 tan θ 12 ) = 12 CE = BC - BE = \frac{6}{\tan \theta} - (\frac{6}{\tan \theta} - 12) = \boxed{12} .

Brian Lie
Aug 8, 2019

This solution is inspired by @Chew-Seong Cheong. Drop an altitude from D D to B C BC and draw a straight line parallel to B C BC through A . A. { A D G C A B D G A B = A G B C D E F C A B E F A B = D F B C D G + E F A B = A G + D F B C = B F + C F B C = 1 C E = C F + E F = D F + E F = F G + D G + E F = A B + A B = 12 . \begin{aligned} &\left\{ \begin{aligned} \triangle{ADG}\sim\triangle{CAB}\implies\frac{DG}{AB}=\frac{AG}{BC}\\ \triangle{DEF}\sim\triangle{CAB}\implies\frac{EF}{AB}=\frac{DF}{BC} \end{aligned} \right.\\\\ \implies & \frac{DG+EF}{AB}=\frac{AG+DF}{BC}=\frac{BF+CF}{BC}=1\\\\ \implies & CE=CF+EF=DF+EF=FG+DG+EF=AB+AB=\boxed{12}. \end{aligned}

Let D H = y \overline{DH}=y . As A H \overline{AH} bisects D A G \angle DAG and A H D G \overline{AH} \perp \overline{DG} , D H H G \overline{DH} \cong \overline{HG} . As H F = 6 \overline{HF}=6 , then F G = 6 y \overline{FG}=6-y . As D F C \bigtriangleup DFC is isosceles, F C = 6 + x \overline{FC}=6+x .

Then, as E F D G F C \bigtriangleup EFD \sim \bigtriangleup GFC we have:

x 6 y 6 + y = 6 y 6 + y \frac{x-6-y}{6+y}=\frac{6-y}{6+y} x = 12 x=12

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...